Sanctioned to Death? The Impact of Economic Sanctions on Life Expectancy and its Gender Gap - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (University of Hamburg, Institute of Law and Economics (ILE), 2017)
In this paper, we empirically analyze the effect of UN and US economic sanctions on life expectancy and its gender gap in target countries. Our sample covers 98 less developed and newly industrialized countries over the period 1977–2012. We employ a matching approach to account for the endogeneity of sanctions. Our results indicate that an average episode of UN sanctions reduces life expectancy by about 1.2–1.4 years. The corresponding decrease of 0.4–0.5 years under an average episode of US sanctions is significantly smaller. These average effects conceal that the damage to life expectancy is accumulating over time; with every additional year under UN (US) sanctions the size of the adverse effect on life expectancy increases by 0.3 (0.2) years. Finally, we find evidence that women are affected more severely by the imposition of sanctions. The fact that sanctions are not “gender-blind” can be interpreted as evidence that sanctions disproportionately affect (the life expectancy of) the more vulnerable members of society.
Keywords: F51; F52; F53; I15; 330; Gender Gap; Human Development; Life Expectancy; Sanctions; United Nations; United States